Emotionally Focused Coping Behavior as a Form of Coping with Stress for Adolescents Experiencing Toxic Parenting Viewed from an Islamic Perspective - Badriyah, Lailatul; Mahdi, Imam; Iqbal, Moch (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
This article aims to explain stress coping carried out by teenagers who experience problems in the family, especially parenting parents who tend to be toxic (hurt children's souls) consciously or unconsciously. In an effort to overcome the pressure caused by toxic parenting, teenagers carry out stress coping strategies to reduce their feelings of pressure. The research method used a qualitative approach, there were 10 informants with an age range of 14-19 years. The research location is Padang Tepong Village, Ulu Musi District, Empat Lawang Regency, South Sumatra. The sampling technique uses purposive sampling. Data was taken through direct interviews and analyzed and validated using the data source triangulation method. The results of this research show that forms of toxic parenting are carried out by parents, such as labeling children as lazy, stupid, comparing children, scolding children, constantly bringing up and taking into account the costs that have been spent on children, making children feel unloved, ignoring children's feelings, controlling their lives too much. children, neglect and loss of the role of parents in children's lives. The dominant stress coping strategy is directed towards emotion focused coping distancing.Keywords – Coping With Stress, Parenting, Toxic Parents.